2016
DOI: 10.1108/so-09-2015-0022
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation: an analysis of twelve years of research

Abstract: Purpose – The purpose of this paper is to explore patterns and developments in the open innovation literature. Design/methodology/approach – A bibliometric analysis was performed by classifying 411 articles in a range of key attributes. Findings – Europe (61 per cent) as a region of data source was higher than all other regions together. As a unit of analysis, firm level (65 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Analysing the type of documents indicates that 65.5% (36) are empirical and approximately 34.5% (19) are theoretical. Several aspects of the empirical documents have been analysed, such as the type of study (Table 6), analytical techniques used (Table 7), and sources of information (Table 8).…”
Section: Methodological Characteristics Of the Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing the type of documents indicates that 65.5% (36) are empirical and approximately 34.5% (19) are theoretical. Several aspects of the empirical documents have been analysed, such as the type of study (Table 6), analytical techniques used (Table 7), and sources of information (Table 8).…”
Section: Methodological Characteristics Of the Documentsmentioning
confidence: 99%
“…We have found literature reviews about open data using different methodologies and temporal scopes [12][13][14][15]. Other studies analyse the literature on open innovation, combining several methodologies and temporal scopes, with 2017 being the last year analysed in the most current articles [16][17][18][19][20][21][22][23][24][25]. Finally, we have found that some of these studies have identified interest in the relationship between the terms "open data" and "open innovation" [12,14,17].…”
Section: Introductionmentioning
confidence: 99%
“…The interface between respective stakeholders becomes an important study object in boundary-crossing innovation activity [25] [57] [58]. Challenges firms face involving external actors in OI have become a popular area for research [11] [12] [13] [14]. Lane & Lubatkin (1998) Open innovation goes beyond the boundaries of the focal firm [58] [59] and recent publications have persistently stressed the necessity of understanding the organizational and contextual factors that moderate the relationship between OI and innovation performance [23].…”
Section: Extant Literature On the Relationship Between Open Innovatiomentioning
confidence: 99%
“…Challenges that firms face involving external actors in OI have become a popular area for research [11] [12] [13] [14]. The rationale of an organization to select the best partner organization among multiple candidates who are having the required knowledge cannot be explained by existing theories [15] [16] [17].…”
Section: Introductionmentioning
confidence: 99%
“…Randhawa et al (2016) offers a bibliometric review that combines the co-citation and text mining techniques to examine 321 articles on OI. Similarly, other studies conduct bibliometric analysis to investigate the development of the OI literature (Hossain and Anees-ur-Rehman 2016;. Seguí-Mas et al (2016) present a bibliometric analysis of OI and absorptive capacity, while Medeiros et al (2016) present a systematic review of the literature on OI in the food industry through a bibliometric analysis.…”
Section: Theoretical Backgroundmentioning
confidence: 99%